Level of Specific Respiratory Syncytial Virus IgA and Interferon Gamma in Serum of Children with RSV - Fahad Rajab Alfahdawi,; Dr Noor Naji Alhayani,; Dr Rana fahmi shetran, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: An estimated 33 million children under the age of five worldwide are projected to be infected with the respiratory syncytial virus (RSV), with 10% of those cases necessitating hospital admission and up to 199,000 deaths from the illness.The most prevalent clinical condition seen with RSV infection is an upper respiratory infection known as bronchiolitis, a lower respiratory tract illness with small airway blockage that can rarely lead to pneumonia, respiratory failure, apnea, and death. Patients and Method:This study involve 58 child infected have been diagnosed infected with RSV, 43 (74.14%) were RSV serotype B and 15 (25.86) were serotype A clinicallywith the help of pediatrician and laboratory by PCR method , The study was conducted at the Ramadi Teaching Hospital for Maternity and Children /Al-Anbar Governorate in period ranging from 1 December 2023 to 15 March 2024. Specific IgA and IFN gamma were detected in serum of infected children their age ranging from 1 months to under 5 years. Result: In this study, we examine 100 cases of probable RSV.Out of 100 cases 58 child were infected with positive RSV . The major infection was recorded by serotype B 43 (74.1%) while, 15(25.8%) with serotype A, 45 positive for specific RSV IgA test and 28 positive for INF-Y test confirm by ELISA technique. Statistical analysis was performed on data from RSV-infected patients as well as age subgroup populations. Patients were classified into the following age groups: 1–6 monthsN=36(36%), 6 to 12 months N=24(24%), 12 to 18months N=9 (9%) , 18 to 24 months N=17(17%), and more than24 months N=14(14%) . Conclusion:The variability in specific RSV IgA and IFN-Gamma responses suggests that immune function differs significantly among individuals. This variability may be related to disease progression, susceptibility, or response to treatments such as antivirals or vaccines.